John Rechy's Sodomites - Ernest, Samuel (Literature and theology, 2021)
Current church debates and queer scholarship unearth Sodom as a site for contesting the relationships between sexuality, religion, queerness, and destruction. In John Rechy's novels City of Night and Numbers, the Sodom story provides an archetype for the books' hustler narrators, whose insatiable desires draw them repeatedly back into "the city of night of the soul", and ultimately, oblivion. Drawing on Heather Love and Catherine Keller, I read Rechy as adapting the Sodom story rather than rejecting it in favour of progress or liberation, as do many queer biblical interpreters and theologians. Rechy's hustlers display a sodomitic subjectivity in their refusal to be whole, which has made his relation to gay/queer and Chicanx literary canons uneasy. Precisely in his "backwardness", Rechy illustrates how theological categories continue to shape gay/queer identities in the 20th century and today.